ENTRE CIDADE E CAMPO: AS SEGUNDAS RESIDÊNCIAS NO ESPAÇO RURAL - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
The thesis has as research object the houses of second home of the rural zone. The study is carried out from city residents in Ponta Grossa (PR), owners of country houses in the rural area of the districts of the municipality. It was sought to understand from these subjects - urban dwellers - what motivates the acquisition of the second home in the countryside. Divided into three chapters, the first part of the research deals with cultural discussions, the search to experiment the rural way of life and new experiences possible within a specific spatial and cultural context. A discussion is show about the concepts of territory, identity and culture, about the process of territorialization through the appropriation / symbolic construction of the space and the experience of the multiterritoriality by the residents of second home is established. The second part seeks to understand the motives of the "escape" of the city and presents a discussion about the historical relation, in the cultural-symbolic aspect, of the relation of the human being with the cities, with the field and the rupture of the relation human being-nature. In the third part, the influence of leisure activities and tourism on the acquisition of secondary home is approached, since, although similar, the actions of having a second residence and practicing tourism in the countryside differ, especially in the sentimental aspects that surround the house. Concepts such as culture, identity, countryside and city, rural and urban relations, memory and patrimony to understand and, with this, to collaborate with the conceptual enlargement and discussion about second homes in the countryside.
Keywords: segunda residência; cultura; campo e cidade; rural e urbano; patrimônio cultural rural; second home; culture; countryside and city; rural and urban; rural cultural heritage; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA